HUBUNGAN STRES DENGAN KEJADIAN HIPERTENSI PADA IBU HAMIL PRIMIGRAVIDA - Ristiani; Sihaloho, Endang (Universitas Sam Ratulangi, 2024)
Background: Hypertension in pregnant women (preeclampsia or eclampsia) is a serious health problem that can occur during pregnancy. Hypertension in pregnant women is a condition of increased blood pressure that occurs after 20 weeks of gestation. This condition can have a serious impact on the health of the mother and the fetus she is carrying. Objective: This study aims to determine the relationship between stress and the incidence of hypertension in primigravida pregnant women. Method: This research design is quantitative research with an analytical survey method using a cross-sectional approach. The population in this study was all pregnant women who came for pregnancy check-ups, namely 172 people. The sampling technique used purposive sampling, the sample size was 75 respondents. Results: There is a significant relationship between stress and the incidence of hypertension in pregnant women (P < 0.05).Conclusion: High level of stress in pregnant women can increase the risk of hypertension during pregnancy. Therefore, healthcare professionals need to pay attention to stress factors in the management of maternal health to prevent hypertension occurrences. Keywords: Hypertension; Pregnant Women; Stress